123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133134135136137138139140141142143144145146147148149150151152153154155156157158159160161162163164165166167168169170171172173174175176177178179 |
- """
- If the arbitrary constant class from issue 4435 is ever implemented, this
- should serve as a set of test cases.
- """
- from sympy.core.function import Function
- from sympy.core.numbers import I
- from sympy.core.power import Pow
- from sympy.core.relational import Eq
- from sympy.core.singleton import S
- from sympy.core.symbol import Symbol
- from sympy.functions.elementary.exponential import (exp, log)
- from sympy.functions.elementary.hyperbolic import (cosh, sinh)
- from sympy.functions.elementary.miscellaneous import sqrt
- from sympy.functions.elementary.trigonometric import (acos, cos, sin)
- from sympy.integrals.integrals import Integral
- from sympy.solvers.ode.ode import constantsimp, constant_renumber
- from sympy.testing.pytest import XFAIL
- x = Symbol('x')
- y = Symbol('y')
- z = Symbol('z')
- u2 = Symbol('u2')
- _a = Symbol('_a')
- C1 = Symbol('C1')
- C2 = Symbol('C2')
- C3 = Symbol('C3')
- f = Function('f')
- def test_constant_mul():
- # We want C1 (Constant) below to absorb the y's, but not the x's
- assert constant_renumber(constantsimp(y*C1, [C1])) == C1*y
- assert constant_renumber(constantsimp(C1*y, [C1])) == C1*y
- assert constant_renumber(constantsimp(x*C1, [C1])) == x*C1
- assert constant_renumber(constantsimp(C1*x, [C1])) == x*C1
- assert constant_renumber(constantsimp(2*C1, [C1])) == C1
- assert constant_renumber(constantsimp(C1*2, [C1])) == C1
- assert constant_renumber(constantsimp(y*C1*x, [C1, y])) == C1*x
- assert constant_renumber(constantsimp(x*y*C1, [C1, y])) == x*C1
- assert constant_renumber(constantsimp(y*x*C1, [C1, y])) == x*C1
- assert constant_renumber(constantsimp(C1*x*y, [C1, y])) == C1*x
- assert constant_renumber(constantsimp(x*C1*y, [C1, y])) == x*C1
- assert constant_renumber(constantsimp(C1*y*(y + 1), [C1])) == C1*y*(y+1)
- assert constant_renumber(constantsimp(y*C1*(y + 1), [C1])) == C1*y*(y+1)
- assert constant_renumber(constantsimp(x*(y*C1), [C1])) == x*y*C1
- assert constant_renumber(constantsimp(x*(C1*y), [C1])) == x*y*C1
- assert constant_renumber(constantsimp(C1*(x*y), [C1, y])) == C1*x
- assert constant_renumber(constantsimp((x*y)*C1, [C1, y])) == x*C1
- assert constant_renumber(constantsimp((y*x)*C1, [C1, y])) == x*C1
- assert constant_renumber(constantsimp(y*(y + 1)*C1, [C1, y])) == C1
- assert constant_renumber(constantsimp((C1*x)*y, [C1, y])) == C1*x
- assert constant_renumber(constantsimp(y*(x*C1), [C1, y])) == x*C1
- assert constant_renumber(constantsimp((x*C1)*y, [C1, y])) == x*C1
- assert constant_renumber(constantsimp(C1*x*y*x*y*2, [C1, y])) == C1*x**2
- assert constant_renumber(constantsimp(C1*x*y*z, [C1, y, z])) == C1*x
- assert constant_renumber(constantsimp(C1*x*y**2*sin(z), [C1, y, z])) == C1*x
- assert constant_renumber(constantsimp(C1*C1, [C1])) == C1
- assert constant_renumber(constantsimp(C1*C2, [C1, C2])) == C1
- assert constant_renumber(constantsimp(C2*C2, [C1, C2])) == C1
- assert constant_renumber(constantsimp(C1*C1*C2, [C1, C2])) == C1
- assert constant_renumber(constantsimp(C1*x*2**x, [C1])) == C1*x*2**x
- def test_constant_add():
- assert constant_renumber(constantsimp(C1 + C1, [C1])) == C1
- assert constant_renumber(constantsimp(C1 + 2, [C1])) == C1
- assert constant_renumber(constantsimp(2 + C1, [C1])) == C1
- assert constant_renumber(constantsimp(C1 + y, [C1, y])) == C1
- assert constant_renumber(constantsimp(C1 + x, [C1])) == C1 + x
- assert constant_renumber(constantsimp(C1 + C1, [C1])) == C1
- assert constant_renumber(constantsimp(C1 + C2, [C1, C2])) == C1
- assert constant_renumber(constantsimp(C2 + C1, [C1, C2])) == C1
- assert constant_renumber(constantsimp(C1 + C2 + C1, [C1, C2])) == C1
- def test_constant_power_as_base():
- assert constant_renumber(constantsimp(C1**C1, [C1])) == C1
- assert constant_renumber(constantsimp(Pow(C1, C1), [C1])) == C1
- assert constant_renumber(constantsimp(C1**C1, [C1])) == C1
- assert constant_renumber(constantsimp(C1**C2, [C1, C2])) == C1
- assert constant_renumber(constantsimp(C2**C1, [C1, C2])) == C1
- assert constant_renumber(constantsimp(C2**C2, [C1, C2])) == C1
- assert constant_renumber(constantsimp(C1**y, [C1, y])) == C1
- assert constant_renumber(constantsimp(C1**x, [C1])) == C1**x
- assert constant_renumber(constantsimp(C1**2, [C1])) == C1
- assert constant_renumber(
- constantsimp(C1**(x*y), [C1])) == C1**(x*y)
- def test_constant_power_as_exp():
- assert constant_renumber(constantsimp(x**C1, [C1])) == x**C1
- assert constant_renumber(constantsimp(y**C1, [C1, y])) == C1
- assert constant_renumber(constantsimp(x**y**C1, [C1, y])) == x**C1
- assert constant_renumber(
- constantsimp((x**y)**C1, [C1])) == (x**y)**C1
- assert constant_renumber(
- constantsimp(x**(y**C1), [C1, y])) == x**C1
- assert constant_renumber(constantsimp(x**C1**y, [C1, y])) == x**C1
- assert constant_renumber(
- constantsimp(x**(C1**y), [C1, y])) == x**C1
- assert constant_renumber(
- constantsimp((x**C1)**y, [C1])) == (x**C1)**y
- assert constant_renumber(constantsimp(2**C1, [C1])) == C1
- assert constant_renumber(constantsimp(S(2)**C1, [C1])) == C1
- assert constant_renumber(constantsimp(exp(C1), [C1])) == C1
- assert constant_renumber(
- constantsimp(exp(C1 + x), [C1])) == C1*exp(x)
- assert constant_renumber(constantsimp(Pow(2, C1), [C1])) == C1
- def test_constant_function():
- assert constant_renumber(constantsimp(sin(C1), [C1])) == C1
- assert constant_renumber(constantsimp(f(C1), [C1])) == C1
- assert constant_renumber(constantsimp(f(C1, C1), [C1])) == C1
- assert constant_renumber(constantsimp(f(C1, C2), [C1, C2])) == C1
- assert constant_renumber(constantsimp(f(C2, C1), [C1, C2])) == C1
- assert constant_renumber(constantsimp(f(C2, C2), [C1, C2])) == C1
- assert constant_renumber(
- constantsimp(f(C1, x), [C1])) == f(C1, x)
- assert constant_renumber(constantsimp(f(C1, y), [C1, y])) == C1
- assert constant_renumber(constantsimp(f(y, C1), [C1, y])) == C1
- assert constant_renumber(constantsimp(f(C1, y, C2), [C1, C2, y])) == C1
- def test_constant_function_multiple():
- # The rules to not renumber in this case would be too complicated, and
- # dsolve is not likely to ever encounter anything remotely like this.
- assert constant_renumber(
- constantsimp(f(C1, C1, x), [C1])) == f(C1, C1, x)
- def test_constant_multiple():
- assert constant_renumber(constantsimp(C1*2 + 2, [C1])) == C1
- assert constant_renumber(constantsimp(x*2/C1, [C1])) == C1*x
- assert constant_renumber(constantsimp(C1**2*2 + 2, [C1])) == C1
- assert constant_renumber(
- constantsimp(sin(2*C1) + x + sqrt(2), [C1])) == C1 + x
- assert constant_renumber(constantsimp(2*C1 + C2, [C1, C2])) == C1
- def test_constant_repeated():
- assert C1 + C1*x == constant_renumber( C1 + C1*x)
- def test_ode_solutions():
- # only a few examples here, the rest will be tested in the actual dsolve tests
- assert constant_renumber(constantsimp(C1*exp(2*x) + exp(x)*(C2 + C3), [C1, C2, C3])) == \
- constant_renumber(C1*exp(x) + C2*exp(2*x))
- assert constant_renumber(
- constantsimp(Eq(f(x), I*C1*sinh(x/3) + C2*cosh(x/3)), [C1, C2])
- ) == constant_renumber(Eq(f(x), C1*sinh(x/3) + C2*cosh(x/3)))
- assert constant_renumber(constantsimp(Eq(f(x), acos((-C1)/cos(x))), [C1])) == \
- Eq(f(x), acos(C1/cos(x)))
- assert constant_renumber(
- constantsimp(Eq(log(f(x)/C1) + 2*exp(x/f(x)), 0), [C1])
- ) == Eq(log(C1*f(x)) + 2*exp(x/f(x)), 0)
- assert constant_renumber(constantsimp(Eq(log(x*sqrt(2)*sqrt(1/x)*sqrt(f(x))
- /C1) + x**2/(2*f(x)**2), 0), [C1])) == \
- Eq(log(C1*sqrt(x)*sqrt(f(x))) + x**2/(2*f(x)**2), 0)
- assert constant_renumber(constantsimp(Eq(-exp(-f(x)/x)*sin(f(x)/x)/2 + log(x/C1) -
- cos(f(x)/x)*exp(-f(x)/x)/2, 0), [C1])) == \
- Eq(-exp(-f(x)/x)*sin(f(x)/x)/2 + log(C1*x) - cos(f(x)/x)*
- exp(-f(x)/x)/2, 0)
- assert constant_renumber(constantsimp(Eq(-Integral(-1/(sqrt(1 - u2**2)*u2),
- (u2, _a, x/f(x))) + log(f(x)/C1), 0), [C1])) == \
- Eq(-Integral(-1/(u2*sqrt(1 - u2**2)), (u2, _a, x/f(x))) +
- log(C1*f(x)), 0)
- assert [constantsimp(i, [C1]) for i in [Eq(f(x), sqrt(-C1*x + x**2)), Eq(f(x), -sqrt(-C1*x + x**2))]] == \
- [Eq(f(x), sqrt(x*(C1 + x))), Eq(f(x), -sqrt(x*(C1 + x)))]
- @XFAIL
- def test_nonlocal_simplification():
- assert constantsimp(C1 + C2+x*C2, [C1, C2]) == C1 + C2*x
- def test_constant_Eq():
- # C1 on the rhs is well-tested, but the lhs is only tested here
- assert constantsimp(Eq(C1, 3 + f(x)*x), [C1]) == Eq(x*f(x), C1)
- assert constantsimp(Eq(C1, 3 * f(x)*x), [C1]) == Eq(f(x)*x, C1)
|